1986
DOI: 10.1002/ajh.2830210306
|View full text |Cite
|
Sign up to set email alerts
|

Fibers, crystals, and other forms of HbS polymers in deoxygenated sickle erythrocytes

Abstract: We have examined by electron microscopy the formation of fibers and crystals from sickle hemoglobin within sickle erythrocytes following deoxygenation during capillary storage from 1 to 132 days. Intracellular fibers were found on the first day and throughout the period of study. The fibers exhibited a diameter (mean +/- SD) of 17.4 +/- 0.62 nm and were aligned in the cell with a fiber-to-fiber spacing of 18.6 nm (x-axis) by 22.7 nm (y-axis). Between 65 and 132 days, extracellular hemoglobin crystals developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…After nucleation, which depends on the 10th power of HbS concentration (i.e., an increase from 86 to 87 g=L would result in a more than a 12% increase of the effective concentration), fibrillar strands are formed that have been clearly demonstrated in the present case. Similar light and electron microscopic studies of sickle cells are known [9][10][11][12][13][14]. It is obvious that in the present case, anesthesia and=or surgery caused a fatal reduction of the ratio of HbS gelation delay time=capillary transit time of erythrocytes.…”
Section: Discussionsupporting
confidence: 76%
“…After nucleation, which depends on the 10th power of HbS concentration (i.e., an increase from 86 to 87 g=L would result in a more than a 12% increase of the effective concentration), fibrillar strands are formed that have been clearly demonstrated in the present case. Similar light and electron microscopic studies of sickle cells are known [9][10][11][12][13][14]. It is obvious that in the present case, anesthesia and=or surgery caused a fatal reduction of the ratio of HbS gelation delay time=capillary transit time of erythrocytes.…”
Section: Discussionsupporting
confidence: 76%
“…We found that sickle cells were a good model for mapping oxidative reactions of hemoglobin. Since many of a sickle cell's hemoglobin molecules are in the form of long fibers (Carragher et al, 1988a,b;Kaperonis et al, 1986), their diffusion coefficient becomes negligible. Sickle cells were opsonized with rabbit anti-human erythrocyte IgG and then deoxygenated by bubbling N, through the cell suspension.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted that sickle-cell hemoglobin fibers are frequently polymorphic (Finch et al, 1973;Ohtsuki et al, 1977;Magdoff-Fairchild & Chiu, 1979;Kaperonis et al, 1986;Mu & Magdoff-Fairchild, 1992;Wang et al, 2000), which suggests that the fiber structure may be variable or ill-defined or that it consists of more than one component. There is also evidence that structural transformations may occur in the filaments making up sickle fibers as a consequence of time or other physical factors (Magdoff-Fairchild & Chiu, 1979;Kaperonis et al, 1986;Mu & Magdoff-Fairchild, 1992).…”
Section: Possible Relationship Of the Methemoglobin Fibers To Sickle-mentioning
confidence: 99%
“…There is also evidence that structural transformations may occur in the filaments making up sickle fibers as a consequence of time or other physical factors (Magdoff-Fairchild & Chiu, 1979;Kaperonis et al, 1986;Mu & Magdoff-Fairchild, 1992).…”
Section: Possible Relationship Of the Methemoglobin Fibers To Sickle-mentioning
confidence: 99%